High‐intensity functional training improves functional movement and body composition among cancer survivors: a pilot study. (10th June 2015) - Heinrich, K.M.; Becker, C.; Carlisle, T.; Gilmore, K.; Hauser, J.; Frye, J.; Harms, C.A.
<x xml:space="preserve">Abstract</x> This pilot study investigated feasibility and preliminary efficacy of a high‐intensity functional training (HIFT) group‐exercise programme among adult cancer survivors within 5 years of last cancer treatment. Eight participants were assigned to a 5‐week, 3 days/week HIFT intervention with four testing sessions and 12 workouts along with mobility and stretching exercises. Feasibility was assessed by initiation, adherence, and acceptability. Efficacy was determined by changes from baseline to post‐test in health‐related quality of life, body composition and functional movement. The recruitment rate was 80% and the adherence rate was 75%. Significant improvements were found for emotional functioning (P = 0.042) and body composition (lean mass +3.8 ± 2.1 kg, P = 0.008; fat mass −3.3 ± 1.0 kg, P = 0.001; body fat percentage −4.7 ± 1.2%, P < 0.001). Participants also significantly improved on five of seven functional movements: balance (P = 0.032), carrying a weighted object (P = 0.004), lower body strength and power (P = 0.009), aerobic capacity and endurance (P = 0.039), and perceived difficulty for flexibility (P = 0.012). Five weeks of HIFT training was well‐received and feasible for most cancer survivors, and effective for improving emotional functioning, body composition and functional movement.